The Influence of Problem-Based Learning Game Education Wordwall on the Mathematics Learning Outcomes of Grade V Elementary School Students in Cluster III Mamben Lauk - Hafizin, Muhammad; Hadiyaturrido, Hadiyaturrido; Hadi, Mashal (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Th This study aims to examine the effect of Wordwall-based educational game learning on the mathematics learning outcomes of fifth-grade elementary school students. The background of this research is grounded in the low level of students’ interest and achievement in mathematics, which is largely attributed to the use of conventional teaching methods that tend to be less engaging. Through an educational game-based learning approach, students are expected to become more active, motivated, and better able to understand mathematical concepts, particularly topics that are commonly perceived as difficult. The research employed a quasi-experimental method with a post-test only control group design. The sample consisted of two classes: an experimental class that implemented Wordwall-based educational game media in the learning process, and a control class that applied conventional instructional methods. The research instrument was a mathematics achievement test administered after the completion of the learning activities. The results indicated that the mean score of mathematics learning outcomes in the experimental class was 82.05, while the control class obtained a mean score of 71.67, which was rounded to 72. Based on the t-test analysis, the significance value (Sig. 2-tailed) was 0.000 < 0.05, indicating a highly significant difference between the two groups. Therefore, it can be concluded that educational game-based learning has a positive and significant effect on improving the mathematics learning outcomes of fifth-grade elementary school students.